Peningkatan Produksi Kopi di Desa Huta Tinggi Kabupaten Samosir Dengan Pemanfaatan Limbah Organik - Hengki Mangiring Parulian Simarmata; Henry Dunan Pardede; Doris Yolanda Saragih; Poltak Pardamean Simarmata; Erwin Sirait (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Training on organic fertilizer processing is one solution to increase the amount of coffee production in Huta Tinggi, Samosir Regency. This community service activity aims to increase public knowledge in utilizing waste into organic fertilizer so as to increase the income of farming communities. Activities are carried out with direct assistance to farmer groups by providing theory and direct practice on coffee plantations. This activity received a very good response from farmers because it provided direct practice. Based on the results of interviews after the activity, 95% of participants felt the benefits of the PKM activity and hoped that there would be mentoring in the implementation of the next activity so that problems in the field could be resolved well.